KONSEP EKOLOGI PADA RANCANGAN BALAI LATIHAN PENGOLAHAN SAMPAH DI BANJARBARU - Al Hauri, Ahmad; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The development of the city of Banjarbaru accompanied by an increase in population and community activities resulting. An increase in the amount of garbage produced. The ideal waste processing and sorting needs and active role from the community is still not running optimally, if these conditions are left the amount of waste that can actually be processed more go more to a landfill or waste damaging the environment. The design of the waste management training center uses the ecological concept with the uses of recycled material or reuse material derived from waste or second thing. Ecological concepts are applied by interactive methods that include design elements namely the wall, floor, plafond, interior, and the composition of the mass and landscape. That concept and method is a solution to create a design that can communicate the importance of community care for the environment and waste process.